miR-370-3p Is a Therapeutic Tool in Anti-glioblastoma Therapy but Is Not an Intratumoral or Cell-free Circulating Biomarker - Arulraj Nadaradjane; Joséphine Briand; Gwenola Bougras-Cartron; Valentine Disdero; François M. Vallette; Jean-Sébastien Frenel; Pierre-François Cartron (Elsevier, 2018)
In the last decade, microRNAs (miRs) have been described as biomarkers and therapeutic agents. Based on this finding, our aim here is to know if (1) miRNA-370-3p can be used as a biomarker associated with a favorable survival and if (2) miRNA-370-3p can be used as a therapeutic tool that increases the efficiency of standard anti-GBM treatment. A first approach using the data available on the "Prognostic miRNA Database" indicated that the expression level of miRNA-370-3p in GBM (T-miR-370-3p) is not associated with a prognosis value for survival. A second approach quantifying the expression level of cell-free circulating miRNA-370-3p (cfc-miR-370-3p) also indicated that cfc-miR-370-3p is not associated with a prognosis value for survival. To investigate whether miR-370-3p can be used in vivo to increase the anti-GBM effect of TMZ, we then used the model of LN18-induced GBMs in mice. Our data indicated that the miRNA-370-3p/TMZ treatment was two times more efficient than the TMZ treatment for decreasing the tumor volume. In addition, our study correlated the decrease of tumor volume induced by the miRNA-370-3p/TMZ treatment with the decrease in FOXM1 and MGMT (i.e., two targets of miR-370-3p).Our data thus support the idea that miR-370-3p could be used as therapeutic tool for anti-glioblastoma therapy, but not as a biomarker. Keywords: GBM, miRNA, temozolomide